The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1021/acs.biochem.8b00283
|View full text |Cite
|
Sign up to set email alerts
|

Cyanylated Cysteine Reports Site-Specific Changes at Protein–Protein-Binding Interfaces Without Perturbation

Abstract: To investigate the cyanylated cysteine vibrational probe group’s ability to report on binding-induced changes along a protein–protein interface, the probe group was incorporated at several sites in a peptide of the calmodulin (CaM)-binding domain of skeletal muscle myosin light chain kinase. Isothermal titration calorimetry was used to determine the binding thermodynamics between calmodulin and each peptide. For all probe positions, the binding affinity was nearly identical to that of the unlabeled peptide. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 79 publications
3
25
0
Order By: Relevance
“… 30 32 Replacement of native residues along a binding interface by β-thiocyano-alanine (or cyanylated cysteine, C* for short) is surprisingly nonperturbative both to the protein’s local secondary structure 33 and to protein–protein binding thermodynamics. 25 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 30 32 Replacement of native residues along a binding interface by β-thiocyano-alanine (or cyanylated cysteine, C* for short) is surprisingly nonperturbative both to the protein’s local secondary structure 33 and to protein–protein binding thermodynamics. 25 …”
Section: Introductionmentioning
confidence: 99%
“…We recently reported 25 dramatic changes in the CN stretching IR absorption bands of SCN labels at six different sites on the M13 peptide as CaM wrapped around it. Furthermore, we showed that the artificial C* residues on the target peptide did not substantially perturb the binding between the species.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, binding of calmodulin to peptides has been investigated by IR spectroscopy using an unnatural amino acid (UAA) that was chemically introduced via cyanylated cysteine (-SCN) reporter labels on either CaM or binding peptides. 12,13 …”
Section: Introductionmentioning
confidence: 99%
“…The thiocyanate moiety is generated by chemical modification of the free thiol of an accessible cysteine residue and can thus be inserted at any cysteine site either being a natural residue or resulting from mutagenesis . Previous studies on the influence of the microenvironment on the signature of the SC≡N stretching frequency in proteins showed typical signals at about 2160 cm −1 for labeled ribonuclease S and for the protein calmodulin .…”
mentioning
confidence: 99%